PENGARUH FOTO PRODUK, ONLINE CUSTOMER REVIEW DAN ONLINE CUSTOMER RATING PADA MINAT BELI KONSUMEN DI FASHION OUTLET RANTAUPRAPAT - Dela Septia Rambe; Muhammad Irwansyah Hasibuan; Mhd. Amin (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to analyze the effect of product photos, online customer reviews, and online customer ratings on consumer purchase intention at fashion outlets in Rantauprapat. This research uses a quantitative approach with a survey method by distributing questionnaires to 150 respondents who are fashion outlet consumers. The data analysis technique used is multiple linear regression analysis with the help of SPSS software. Before conducting the analysis, the data were tested using validity, reliability, and classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The results showed that all statement items were valid and reliable. The classical assumption tests also indicated that the data were normally distributed and free from multicollinearity and heteroscedasticity. The results of the t-test showed that product photos have a positive and significant effect on purchase intention with a regression coefficient of 0.382 and a significance value of 0.000. Online customer reviews also have a positive and significant effect on purchase intention with a regression coefficient of 0.418 and a significance value of 0.000. In addition, online customer ratings have a positive and significant effect on purchase intention with a regression coefficient of 0.447 and a significance value of 0.000. The F-test results indicate that product photos, online customer reviews, and online customer ratings simultaneously have a significant effect on purchase intention with an F value of 46.785 and a significance value of 0.000. The coefficient of determination (R Square) of 0.707 indicates that 70.7% of the variation in purchase intention can be explained by these independent variables, while the remaining is influenced by other variables outside this study. Thus, it can be concluded that product photos, customer reviews, and product ratings are important factors in increasing consumer purchase intention.